Strategi Pemasaran Inovatif Produk Kacandipa Dalam Menentukan Potensi Pasar Di Desa Sunju - Tediy Adrian Hermansyah; Syamsul Bahri Dg. Parani; Zakiyah Zahara; Asriadi Asriadi (Institut Nalanda, 2024)
This study aims to investigate innovative marketing strategies for Kacandipa products in Sunju Village using a SWOT analysis approach. By combining qualitative data from scientific literature and observations, we analyzed the internal strengths, weaknesses, opportunities, and threats that affect the marketing of Kacandipa products. The results of the SWOT analysis identified product uniqueness, utilization of local raw materials, strong local reputation as key strengths, while limited distribution and lack of consumer awareness are some of the weaknesses faced. In the face of digital market expansion opportunities and government support, we formulated a TOWS strategy that includes strengthening digital market expansion, supply chain optimization, and increasing consumer awareness. The practical implication of this research is to provide guidance for local businesses to develop effective and sustainable marketing strategies for Kacandipa products in the Sunju Village market and possibly beyond that geographical boundary. It is hoped that the results of this study can contribute to the local marketing literature and provide insights for practitioners in optimizing the market potential of local products.